(untitled) (Eureka Journal of Language, Culture & Social Change, 2026)
The silicate bricks produced by the Nukus and Muynak sand and 15-25% of Aktau and Jumurtau lime were mixed using 75-85% Nukus and Muynak sand, and 15-25% of Aktau and Jumurtau lime. Abstract. This article presents an analysis of the processes and results of the study on all types of silicate brick solidification by autoclave and manipulation. In testing, model mixtures of sand from Nukus and Muynak and 15-25% lime from Aktau and Djumurtau were included.